Correlation of Leukopenia with Vitamin D Levels in Ovarian Cancer Patients Undergoing Platinum-Taxane-Based Chemotherapy - Antonius, Puja Agung; Firdawati, Firdawati; Syamel Muhammad; Karmia, Hudila Rifa; Wijaya, Caesar Muhammad; Yusrawati, Yusrawati (Andalas Obstetrics And Gynecology Journal, 2025)
Introduction: Ovarian cancer is a significant cause of death in women. One of the management of advanced ovarian cancer patients is chemotherapy. The effects of administering Platinum-Taxane-Based chemotherapy to ovarian cancer patients show side effects of myelosuppression, one of which is leukopenia. Methods: This type of study is a correlation analytical study with a cross-sectional design from October 2023 to May 2024 at Dr. M. Djamil Central General Hospital Padang. The patients included were ovarian cancer patients who underwent Platinum-Taxane-Based chemotherapy with laboratory results of leukopenia. Results: From 70 patients, it was found that 37 patients (52.9%) had grade I leukopenia, 27 patients (38.6%) had grade II, and 6 patients (8.6%) had grade III. Based on the results obtained, in grade I leukopenia, the average vitamin D value is 13.162 ng/mL, grade II has an average vitamin D value of 11.851 ng/mL, grade III has an average vitamin D value of 14.333 ng/mL. The study results showed a relationship between leukopenia and vitamin D levels p = 0.034 (p < 0.05). Conclusion: There was a relationship between leukopenia and vitamin D levels in ovarian cancer patients undergoing Platinum-Taxane-Based Chemotherapy at Dr. M. Djamil Central General Hospital Padang.